Antibiotic Resistance Patterns of Bacterial Isolates from Neonatal Sepsis Patients at University Hospital of Leipzig, Germany - Belay Tessema; Norman Lippmann; Matthias Knüpfer; Ulrich Sack; Brigitte König (MDPI AG, 2021)
Neonatal sepsis caused by resistant bacteria is a worldwide concern due to the associated high mortality and increased hospitals costs. Bacterial pathogens causing neonatal sepsis and their antibiotic resistance patterns vary among hospital settings and at different points in time. This study aimed to determine the antibiotic resistance patterns of pathogens causing neonatal sepsis and to assess trends in antibiotic resistance. The study was conducted among neonates with culture proven sepsis at the University Hospital of Leipzig between November 2012 and September 2020. Blood culture was performed by BacT/ALERT 3D system. Antimicrobial susceptibility testing was done with broth microdilution method based on ISO 20776-1 guideline. Data were analyzed by SPSS version 20 software. From 134 isolates, 99 (74%) were gram positive bacteria. The most common gram positive and gram negative bacteria were S. epidermidis, 51 (38%) and E. coli, 23 (17%), respectively. S. epidermidis showed the highest resistance to penicillin G and roxithromycin (90% each) followed by cefotaxime, cefuroxime, imipenem, oxacillin, and piperacillin-tazobactam (88% each), ampicillin-sulbactam (87%), meropenem (86%), and gentamicin (59%). Moreover, S. epidermidis showed raising levels of resistance to amikacin, gentamicin, ciprofloxacin, levofloxacin, moxifloxacin, and cotrimoxazol. Gram positive bacteria showed less or no resistance to daptomycin, linezolid, teicoplanin, and vancomycin. E. coli showed the highest resistance to ampicillin (74%) followed by ampicillin-sulbactam (52%) and piperacillin (48%). Furthermore, increasing levels in resistance to ampicillin, ampicillin-sulbactam, piperacillin, and cefuroxime were observed over the years. Encouragingly, E. coli showed significantly declining trends of resistance to ciprofloxacin and levofloxacin, and no resistance to amikacin, colistin, fosfomycin, gentamicin, imipenem, piperacillin-tazobactam, and tobramycin. In conclusion, this study demonstrates that gram positive bacteria were the leading causes of neonatal sepsis. Bacterial isolates were highly resistant to first and second-line empiric antibiotics used in this hospital. The high levels of antibiotic resistance patterns highlight the need for modifying empiric treatment regimens considering the most effective antibiotics. Periodic surveillance in hospital settings to monitor changes in pathogens, and antibiotic resistance patterns is crucial in order to implement optimal prevention and treatment strategies.